Wstępne doświadczenia w zastosowaniu biodegradowalnych stentów oskrzelowych u dzieci – opis przypadku - Zając, Andrzej; Krysta, Mirosław; Tomasik, Przemysław; Górecki, Wojciech (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Airway malacia is the most common cause of tracheobronchial obstruction in children. It can be congenital or acquired. Aortopexy and surgical relief of external compression are main therapeutical options. An alternative for surgical approach can be metallic airway stents, but usually they are not considered as a first choice, because of relatively high risk of complications. Moreover, metallic airway stents are permanent, so they have limited usage in growing bronchial tree in newborns and neonates. Recent years have brought encouraging reports of application biodegradable stents in children. Authors present the case of 12-months old girl after right pulmonectomy in neonatal period due to congenital cystic adenomatoid malformation (CCAM). In the second half year of life the baby presented increasing dyspnea because of left main bronchus malacia. We decided to implant biodegradable bronchial stent. Polydioxanone (PDS) custom made stent (ELLACS) was placed with good tolerance and quick relief of previous symptoms. After 2 days patient was extubated and now stays in good condition at home.